Gendered Patterns of Lexical Complexity: Evidence from Indonesian EFL Learners - Arif Rahman; Fitriyeni; Nurhayati S (Universitas Islam Negeri Palopo, 2026)
Lexical complexity is a key indicator of writing quality and language proficiency in English as a Foreign Language (EFL) contexts, yet its relationship with gender among Indonesian learners remains underexplored. This study examined lexical complexity in descriptive writing produced by 40 intermediate-level Indonesian EFL learners (20 male, 20 female) drawn from secondary and tertiary institutions. Using a quantitative comparative design, participants completed a controlled descriptive writing task under standardized conditions. Lexical complexity was operationalized through Type-Token Ratio (TTR), total word count, and unique word types, and analyzed via the Lexical Complexity Analyzer (LCA) and independent samples t-tests. Results revealed a low-to-moderate overall complexity level (group mean TTR = 0.497). Significant gender differences emerged across all three measures (p < .001), with female learners consistently outperforming male learners in word count (M = 194.55 vs. 175.40), word types (M = 104.55 vs. 80.00), and TTR (M = 0.537 vs. 0.456). Lexical diversity, measured by TTR, proved the most dominant aspect, yielding the largest effect sizes across all comparisons. These findings position gender as a significant individual difference variable in EFL lexical performance and underscore the need for gender-responsive vocabulary instruction in the Indonesian EFL context.